Compatibility of Education and Training in the Light of The Seerah of the Holy Prophet - Khadija Aziz; Sonea Ambreen (Journal of Islamic and Religious Studies, 2016)
Humankind has been granted a special status due to its being vicegerent of Allah on earth for he has been entrusted with the responsibility to keep order in the world according to the directives of its Creator. Humans are guided by Prophets in history. Some of these Prophets have got greater value, sphere and depth of influence on humanity due to different factors. Muhammad (Peace Be Upon Him) is the last Prophet of Allah, for the eternity and whole humanity. After him, Islam is completed for all times to come. Islam is a complete code of life; education and training constituting its crux. Prophet Muhammad (Peace Be Upon Him) was greatly concerned and cognizant of education and training of his followers which is evident from multifarious events of his life. Major emphasis was laid on training coupled with education and both are, thus, inevitably interlocked with each other. It is clear that education was considered an assimilation of knowledge and training was taken as its reflection in daily life. The verses of the Holy Quran and sayings of the Holy Prophet (Peace Be Upon Him) bear a perfect testimony to this aspect of foremost significance. The earlier people in the fold of Islam were much concerned about training and nurturing, hence they avoided mere memorization of facts. The present paper is an attempt to discover the compatibility between education and training in the light of the paradigm of secret of the Prophet (Peace Be Upon Him) of Islam.